2017
DOI: 10.3389/fphar.2017.00611
|View full text |Cite
|
Sign up to set email alerts
|

Yougui Pills Attenuate Cartilage Degeneration via Activation of TGF-β/Smad Signaling in Chondrocyte of Osteoarthritic Mouse Model

Abstract: Yougui pills (YGPs) have been used for centuries in the treatment of Chinese patients with Kidney-Yang Deficiency Syndrome. Despite the fact that the efficiency of YGPs on treating osteoarthritis has been verified in clinic, the underlying mechanisms are not totally understood. The present study observes the therapeutic role of YGPs and mechanisms underlying its chondroprotective action in osteoarthritic cartilage. To evaluate the chondroprotective effects of YGPs, we examined the impact of orally administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In contrast, the You-gui pill (YGP) is a classic traditional Chinese medicine (TCM) formula for the treatment of KYDS and has been widely used to warm and recuperate KYDS clinically for hundreds of years in China [6]. It was originally described by “Jing-Yue Complete Works” in the year 1624 and consisted of ten herbs, including Radix Rehmanniae Praeparata (SDH, Shu-Di-Huang), Radix Aconiti Lateralis Prreparata (FZ, Fu-Zi), Cinnamomi cortex (RG, Rou-Gui ), Rhizoma Dioscoreae (SY, Shan-Yao), Fructus Corni (SZY, Shan-Zhu-Yu), Semen Cuscutae (TSZ, Tu-Si-Zi), Fructus Lycii (GQ, Gou-Qi), Cervi cornus colla (LJJ, Lu-Jiao-jiao), Eucommiae cortex (DZ, Du-Zhong), and Radix Angeliccae Sinensis (DG, Dang-Gui) [6,7,8]. The ratio of ten herbs in YGP was: SDH (8); SY (4); SZY (3); GQ (4); LJJ (4); TSZ (4); DZ (4); RG (2); FZ (2); DG (3).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the You-gui pill (YGP) is a classic traditional Chinese medicine (TCM) formula for the treatment of KYDS and has been widely used to warm and recuperate KYDS clinically for hundreds of years in China [6]. It was originally described by “Jing-Yue Complete Works” in the year 1624 and consisted of ten herbs, including Radix Rehmanniae Praeparata (SDH, Shu-Di-Huang), Radix Aconiti Lateralis Prreparata (FZ, Fu-Zi), Cinnamomi cortex (RG, Rou-Gui ), Rhizoma Dioscoreae (SY, Shan-Yao), Fructus Corni (SZY, Shan-Zhu-Yu), Semen Cuscutae (TSZ, Tu-Si-Zi), Fructus Lycii (GQ, Gou-Qi), Cervi cornus colla (LJJ, Lu-Jiao-jiao), Eucommiae cortex (DZ, Du-Zhong), and Radix Angeliccae Sinensis (DG, Dang-Gui) [6,7,8]. The ratio of ten herbs in YGP was: SDH (8); SY (4); SZY (3); GQ (4); LJJ (4); TSZ (4); DZ (4); RG (2); FZ (2); DG (3).…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence suggests TCM as being effective in articular cartilage protection. For example, Zhang et al described protective activity for cartilage via reducing the expression of Mmp13 and elevating Col2 with the TCM Yougui pills which were administered to mouse model induced by destabilization of the medial meniscus [ 29 ]. Wang et al reported Bi-Qi capsule alleviated cartilage destruction by downregulating the expression of tumor necrosis factor- α (TNF- α ) and Interleukin-18 (IL-18) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the changes in subchondral bone are related to several signaling pathways such as the Wnt/β-Catenin, TGF-β/Smad, RANK/RANKL/OPG (Receptor activator of nuclear factor kappa-Β, RANK ligand, and osteoprotegerin), and MAPK (mitogen-activated protein kinase) signaling pathways [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Moreover, identification of the molecular pathways involved in OA-related bone remodeling has led to certain therapeutic agents targeting the mechanisms considered as possible DMOADs [ 85 , 86 , 87 , 88 , 89 , 90 ].…”
Section: Therapeutic Approach To Bone Remodeling In Knee Osteoarthmentioning
confidence: 99%